The introduction of Christian Ethics as a topical issue in Ukraine's religious life - Sagan, Oleksandr N. (2005)
Even after 14 years of independence, Ukrainian society has not lost many of its problems, which are rooted in the legacy of Soviet militant atheism. One of the problems that has caused heated debate in religious and educational settings in almost all years of independence is the perception / non-acceptance of the need for religious education by secular school students. Against the backdrop of equally acute property problems related to the return to religious buildings of the Church, disputes about the status and content of religious courses have been leading in relevance for the last five to six years.
Українське суспільство і через 14 років незалежності не позбавилося багатьох проблем, корені яких ховаються у спадку радянського войовничого атеїзму. Однією із таких проблем, яка практично всі роки незалежності викликає гострі дискусії в релігійному та освітянському середовищах, є сприйняття/несприйняття потреби в релігійній освіті школярів світських навчальних закладів. На тлі не менш гострих майнових проблем, пов‘язаних із поверненням Церквам культових споруд, суперечки про статус та зміст релігійних курсів останні п‘ять-шість років лідирують за своєю актуальністю.